Plant Nutrition 2001
DOI: 10.1007/0-306-47624-x_343
|View full text |Cite
|
Sign up to set email alerts
|

Corn stalk nitrate concentration profile: Implications for the end-of-season stalk nitrate test

Abstract: and Schepers, James S., "Corn stalk nitrate concentration profile: Implications for the end-of-season stalk nitrate test" (2001 AbstractThe end-of-season corn (Zea mays L.) stalk nitrate-N test was developed as a post-mortem to determine if excessive or insufficient N was available to the corn crop during the latter part of the season. The stalk section specified for the test was very specific, the 20 cm-long section between 15 and 35 cm above the soil. Under production conditions, it may not always be possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The mean concentration of samples taken from the no manure or FN control ranged from non‐detectable to as high as 5013 mg NO 3 –N kg −1 . This wide range in concentrations was also reported by previous studies (Wilhelm et al, 2001; Isla and Blackmer, 2007) and indicates variation in soil N supply. Fertilizer N applied alone increased the CSNT at only 9 of 16 sites (Table 7), despite the more frequent GY (Table 5) and RCM (Table 6) response to FN.…”
Section: Resultssupporting
confidence: 88%
“…The mean concentration of samples taken from the no manure or FN control ranged from non‐detectable to as high as 5013 mg NO 3 –N kg −1 . This wide range in concentrations was also reported by previous studies (Wilhelm et al, 2001; Isla and Blackmer, 2007) and indicates variation in soil N supply. Fertilizer N applied alone increased the CSNT at only 9 of 16 sites (Table 7), despite the more frequent GY (Table 5) and RCM (Table 6) response to FN.…”
Section: Resultssupporting
confidence: 88%
“…The second concern is the impact of error in sample collection. That is, what is the impact of collecting a sample lower or higher on the stalk than specified by Binford et al (1990) Lastly, for several reasons (Wilhelm et al, 2001), we have found collecting samples composed of one phytomer from the base of the stalk more convenient than following the procedures outlined by Binford et al (1990) The reasons include our concern about relative tissue component of the sample and ease of sample handling. Frequently we collect stalk nitrate samples in conjunction with plant dry matter sampling.…”
Section: Resultsmentioning
confidence: 99%
“…Regressing sample NO 3 –N concentrations from the standard sampling procedure against the concentrations for the first phytomer resulted in slopes of 1.57 and 1.21 for the dryland and irrigated studies, respectively. As suggested by Wilhelm et al (2001), an increase in critical values of 35 to 40% would be appropriate when sampling lower parts of the stalk. This adjustment would result in critical values of 950 to 1000 and 2700 to 3000 mg NO 3 –N kg −1 for the break points between N‐limited yield and adequate N for optimum yield and adequate N for optimum yield and N in excess of that needed for optimum yield.…”
Section: Resultsmentioning
confidence: 99%
“…Each sample was divided into four quarters and one quarter was retained, dried at 60°C, and then ground to pass a 2-mm screen prior to NO 3 analysis. Extractable NO 3 was analyzed with 0.05 mol L -1 Al 2 (SO 4 ) 3 and a 2 mol L -1 (NH 4 ) 2 SO 4 ionic strength adjustor according to Wilhelm et al (2001). A nitrate-selective electrode and a 710A pH/ISE meter (Thermo Scientific Orion, Waltham, MA) were used.…”
Section: Corn Stalk Nitrate Testmentioning
confidence: 99%